Perancangan Aplikasi Mobile Konsultasi Kesehatan Berbasis Android Studio Di Rumah Sakit Universitas Riau - Anashroh Rizkiyah Siregar; Ery Safrianti; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Riau University hospital is an educational infrastructure institution and health institution in collaboration with Riau University. Most of the patients treated at Riau University hospital are people from the riau university community such as campus staff, lecturers and students. Outside communities that are not from the community of UNRI campus have a small percentage to treat in hospitals Riau University. Another problem, for patients who are located far from the hospital of Riau University will have difficulty because patients who want to seek treatment at the University of Riau hospital and conduct consultations with the desired doctor can not know the schedule of the doctor on duty, so the patient must go to the hospital first to find out the schedule of the doctor's duties on the day. Therefore, a consultation application is needed that can help solve the problems described. This research uses waterfall method to help the process of making consulting application. The data collection is obtained by interview method and observation directly to the field. The consulting application was created using Android Studio with the Java programming language and eXtensible Markup Language (XML), as well as Firebase as a database. Application testing uses the User Acceptance Test (UAT) method to see the results of application creation based on user ratings. Based on the results and tests carried out, obtained an android-based UNRI hospital consultation application. This consultation application can be used by patients to view schedules and consult online with doctors working in UNRI hospitals. This application is expected to help prospective patients can seek treatment and consult a doctor easily. Keyword : Java, XML, Android